2020
DOI: 10.32548/2020.me-04183
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of High-Temperature Hydrogen Attack Using Advanced Ultrasonic Array Techniques

Abstract: The ability to measure early-stage high-temperature hydrogen attack (HTHA) has been improved by the use of optimized ultrasonic array probes and techniques. First, ultrasonic modeling and simulations were performed to design a set of array probes. The data was then collected using phased array ultrasonic testing (PAUT) and full matrix capture (FMC) techniques. Damage visualization, characterization, and sizing was completed with PAUT, total focusing method (TFM), and adaptive total focusing method (ATFM) advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Even though phased array measurements are included in recommended practices, the TFM method allows one to significantly increase the resolution and to detect cracks at earlier stages. It has been demonstrated that TFM can detect stage 2 HTHA with a crack size of 300 µm [23], while the results obtained in this paper support such statements. On the other hand, the results using TULA probes appear to be quite novel and demonstrate that such a technique can be used with similar confidence as TFM.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Even though phased array measurements are included in recommended practices, the TFM method allows one to significantly increase the resolution and to detect cracks at earlier stages. It has been demonstrated that TFM can detect stage 2 HTHA with a crack size of 300 µm [23], while the results obtained in this paper support such statements. On the other hand, the results using TULA probes appear to be quite novel and demonstrate that such a technique can be used with similar confidence as TFM.…”
Section: Discussionsupporting
confidence: 72%
“…Different ultrasonic techniques are frequently used as a primary tool for determining the extent of hydrogen damage, namely, acoustic emission, non-linear ultrasonic testing, Crack Indication Density (CID) method, tri-lateral phased array scanning, advanced veloc-ity ratio (AVR), advanced ultrasonic backscatter technique (AUBT), time of flight diffraction (TOFD), TULA (TOFD ultra low angle) and total focusing method (TFM) [17,[19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%